2023
DOI: 10.1186/s12936-023-04555-w
|View full text |Cite
|
Sign up to set email alerts
|

Availability of malaria diagnostic tests, anti-malarial drugs, and the correctness of treatment: a systematic review and meta-analysis

Abstract: Background Health facilities’ availability of malaria diagnostic tests and anti-malarial drugs (AMDs), and the correctness of treatment are critical for the appropriate case management, and malaria surveillance programs. It is also reliable evidence for malaria elimination certification in low-transmission settings. This meta-analysis aimed to estimate summary proportions for the availability of malaria diagnostic tests, AMDs, and the correctness of treatment. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 41 publications
2
1
0
Order By: Relevance
“…Information from the mRDT improved targeting of ACTs, particularly reducing consumption among those with a negative test. The adherence to test results observed in our study is comparable to studies from the formal health sector [ 34 ] adding to the evidence that case management is not compromised in retail venues compared to formal health facilities. We observed in our study that a quarter of clients who tested positive at the outlet did not receive an ACT (27%).…”
Section: Discussionsupporting
confidence: 84%
“…Information from the mRDT improved targeting of ACTs, particularly reducing consumption among those with a negative test. The adherence to test results observed in our study is comparable to studies from the formal health sector [ 34 ] adding to the evidence that case management is not compromised in retail venues compared to formal health facilities. We observed in our study that a quarter of clients who tested positive at the outlet did not receive an ACT (27%).…”
Section: Discussionsupporting
confidence: 84%
“…16 Information from the mRDT improved targeting of ACTs, particularly reducing consumption among those with a negative test. The adherence to test results observed in our study is comparable to studies from the formal health sector 33 adding to the evidence that case management is not compromised in retail venues compared to formal health facilities. We observed in our study that a quarter of clients who tested positive at the outlet did not receive an ACT (27%).…”
Section: Discussionsupporting
confidence: 83%
“…Studies in several sub-Saharan African countries have shown that private health facilities and drug outlet providers lack knowledge and do not adhere to national malaria case management guidelines [7][8][9][10][11][12]. This was con rmed by recent meta-analyses that reported healthcare provider reliance on clinical malaria diagnosis and low adherence to appropriate malaria case management guidelines [13][14][15]. In Kenya, gaps in knowledge have been reported, with drug outlet providers, in particular, showing a poor understanding of national malaria treatment guidelines and a lack of training in malaria case management [16,17].…”
mentioning
confidence: 99%